Poly-ε-caprolactone nanoparticles loaded with 4-nerolidylcatechol (4-nc) for growth inhibition of microsporum canis - Greatti, Vanessa Raquel [UNESP]; Oda, Fernando [UNESP]; Sorrechia, Rodrigo [UNESP]; Kapp, Bárbara Regina [UNESP]; Seraphim, Carolina Manzato [UNESP]; Weckwerth, Ana Carolina Villas Bôas; Chorilli, Marlus [UNESP]; Da Silva, Patrícia Bento [UNESP]; Eloy, Josimar O.; Kogan, Marcelo J.; Morales, Javier O.; Rodrigues Pietro, Rosemeire Cristina Linhari [UNESP] (MDPI, 2020)
Dermatophyte fungal infections are difficult to treat because they need long-term treatments. 4-Nerolidylcatechol (4-NC) is a compound found in Piper umbellatum that has been reported to demonstrate significant antifungal activity, but is easily oxidizable. Due to this characteristic, the incorporation in nanostructured systems represents a strategy to guarantee the compound’s stability compared to the isolated form and the possibility of improving antifungal activity. The objective of this study was to incorporate 4-NC into polymeric nanoparticles to evaluate, in vitro and in vivo, the growth inhibition of Microsporum canis. 4-NC was isolated from fresh leaves of P. umbellatum, and polymer nanoparticles of polycaprolactone were developed by nanoprecipitation using a 1:5 weight ratio (drug:polymer). Nanoparticles exhibited excellent encapsulation efficiency, and the antifungal activity was observed in nanoparticles with 4-NC incorporated. Polymeric nanoparticles can be a strategy employed for decreased cytotoxicity, increasing the stability and solubility of substances, as well as improving the efficacy of 4-NC.
Keywords: 4-Nerolidylcatechol; Antifungals; Microsporum canis; Nanoparticles; Nanoprecipitation; Polycaprolactone